Cecilia's fundraiser - Avery, Bryan Patrick (Avery, Bryan Patrick. Mr. Grizley's class., 2022)
"Mr. Grizley's class is hosting a fundraiser for the animal shelter. Cecilia is disappointed that she forgot the tamales she was going to sell. Can her classmates come to the rescue and help her make a new plan? "--